TANTANGAN KEPEMIMPINAN DI DAERAH - Refian Garis, Regi; Diah Suciati; Andi Wardani; Rusli (Journal Education and Government Wiyata, 2023)
Collaboration between central and regional leadership is important to achieve common goals and improve the quality of life of the community. The purpose of this study is to find out how leadership is implemented in the regions. The method used is the study of literature from various sources, such as books and scientific journal articles. The results of the discussion are as follows: Some of the advantages of collaboration between central and regional leadership Better use of resources: With collaboration between the center and the regions, existing resources can be better utilized to achieve common goals. The two can support each other in terms of financing, human resources, and technology. Government performance improvement: Collaboration between the center and the regions can help improve government performance in terms of public services and better decision making. Both can learn from each other and exchange experiences to improve overall government performance. Increasing community participation: With collaboration between the center and the regions, community participation can increase. Communities are becoming more involved in decision-making processes and implementing programs implemented by the government. Improved coordination and synergy: Collaboration between the center and regions can improve coordination and synergy between various government agencies. This can help accelerate the implementation of programs and policies taken. Improving development equity: Collaboration between the center and the regions can help increase the distribution of development in all regions of Indonesia. With good coordination, programs and policies can be implemented more evenly and reach all regions in Indonesia.